2019
DOI: 10.2217/fon-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

Impassion132 Phase Iii Trial: Atezolizumab And Chemotherapy In Early Relapsing Metastatic Triple-Negative Breast Cancer

Abstract: The PD-L1 inhibitor atezolizumab received US FDA accelerated approval as treatment for PD-L1-positive metastatic triple-negative breast cancer (TNBC). In IMpassion130, combining atezolizumab with first-line nab-paclitaxel for metastatic TNBC significantly improved progression-free survival and showed a clinically meaningful effect on overall survival in patients with PD-L1-positive tumors. The placebo-controlled randomized Phase III IMpassion132 (NCT03371017) trial is evaluating atezolizumab with first-line ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 30 publications
1
52
0
1
Order By: Relevance
“…28 Results from the phase III IMpas-sion132 trial evaluating atezolizomib with several chemotherapies including capecitabine as first-line therapy for TN MBC will contribute to our understanding of the use of chemo-immunotherapy in metastatic TNBC. 29 For HR+ endocrine-refractory MBC, there is more limited data for chemo-immunotherapy. One phase II study of eribulin and pembrolizumab compared with pembrolizumab alone demonstrated no improvement in PFS.…”
Section: Discussionmentioning
confidence: 99%
“…28 Results from the phase III IMpas-sion132 trial evaluating atezolizomib with several chemotherapies including capecitabine as first-line therapy for TN MBC will contribute to our understanding of the use of chemo-immunotherapy in metastatic TNBC. 29 For HR+ endocrine-refractory MBC, there is more limited data for chemo-immunotherapy. One phase II study of eribulin and pembrolizumab compared with pembrolizumab alone demonstrated no improvement in PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, thanks to of the continuous effort in searching molecularly targeted approaches for TNBC, the first targeted therapies have been recently approved. These consist in the PARP inhibitors Olaparib or Talazoparib [6], which is beneficial for BRCA-mutated patients but efficiently target TNBC cells regardless of the BRCA-status, and the anti-programmed cell death-ligand 1 (PD-L1) Atezolizumab plus nab-paclitaxel chemotherapy [7], which applies to patients with unresectable locally advanced or metastatic PD-L1-positive TNBCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, IMpassion 132 (NCT03371017) focuses on patients with early relapsing TNBC and evaluates the efficacy and safety of combining atezolizumab with non-taxane (gemcitabine plus carboplatin or capecitabine alone). 89 This trial should indicate whether similar improvements can be achieved with an alternative chemotherapy regimen in patients with early relapsing TNBC.…”
Section: Combination Therapymentioning
confidence: 97%